Kadar antioksidan superoksida dismutase (SOD) hati tikus pada aktivitas fisik berat - I Putu Prananta Andi Yunarsa; I Putu Gede Adiatmika (E-Jurnal Medika Udayana, 2018)
Heavy physical activity will be increased the production of free radicals or reactive oxygen species (ROS) in the body, so it can decreased intracellular antioxidant enzymes liver, including superoxide dismutase (SOD). This study aims to determine antioxidant superoxide dismutase activity in liver on heavy physical activity. This research was a laboratory experiment with randomized post-test only control group design. This study was used of 20 male rats albino Wistar strain with an average body weight of 200 g. Rats were divided into two groups, without treatment or control treatment (K1) and treatment with heavy physical activity (K2). Heavy physical activity treatment are given swimming for one hour/day. This research was carried out for 3 weeks. At the end of the treatment, all rats ware sacrificed by euthanasia using ketamine-HCl 1 mL/200 g bw. Rat liver were taken and divided into two, namely for SOD level analysis and for immunohistochemical staining. Data were analyzed by independent t test. The results showed that treatment of heavy physical activity have a negative impact. Level of SOD in rat liver tissue by 34.84% lower compared to the control treatment (K1) of 68.39% (p<0.01). By immunohistochemistry, on liver tissue of normal control rats (K1), qualitatively appear SOD react positively on nucleus and the cytoplasm with a strong brown color intensity compared to liver tissue rat with heavy physical activity treatment (K2). It can be concluded that heavy physical activity can reduce level of SOD enzyme in the liver. Keywords: heavy physical activity, SOD, free radical, oxidative stress.